The use of digital flashcards as a learning strategy to foster the mastery of vocabulary in oral production tasks through Task-Based an approach in a virtual EFL classroom in a group of seventh grade students at Esparza High school - Alvarado Rodríguez, Jennifer Tatiana 1993- (2021)
This research encompasses the use of digital flashcards to foster the mastery of vocabulary in oral production tasks. To carry out this study, the researchers conducted different instruments in order to obtain the results, analyze the data, and verify if the objectives were fulfilled. The main aim is to analyze the effectiveness of digital flashcards as a learning strategy to improve the mastery of vocabulary; thus, to make students communicate better in the second language.